2006
DOI: 10.1021/jp060702w
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Codoping Effects on the Solubility Enhancement of Er3+ in SiO2 Glass:  Striking Difference between Al and P Codoping

Abstract: The codoping effect mechanism of Al and P on the solubility enhancement of Er(3+) ion in SiO(2) glass was clarified by electron spin-echo envelope modulation spectroscopy. It turned out that doped P ions preferentially coordinate to the Er(3+) ion to form a "solvation shell structure", and the environment is similar to that in phosphate glass, while doped Al ions do not form such a selective solvation structure, taking octahedral coordination. This striking difference indicates that the primary roles of the P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 24 publications
2
57
3
Order By: Relevance
“…Monteil et al 71 72) proposed that the oxygen coordination number of Al should be 6 based on the coordination in alkali-free aluminosilicate crystals and glasses. 73),74) Saitoh et al 75) elucidated the local structure around an Er 3+ ion using electron spin echo envelope modulation (ESEEM) spectroscopy. ESEEM spectroscopy is a powerful tool because it can determine the distance and coordination number of ligands in a mediumrange structure because very fine interference signals, which are unresolved in conventional continuous wave (CW)-electron paramagnetic resonance (EPR) spectroscopy, are observable by time domain measurements; i.e., it provides information on the medium-range structure around a specific paramagnetic species and quantitative results are obtained by a simulation of the spectrum shape.…”
Section: Mechanism Of Codoping Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Monteil et al 71 72) proposed that the oxygen coordination number of Al should be 6 based on the coordination in alkali-free aluminosilicate crystals and glasses. 73),74) Saitoh et al 75) elucidated the local structure around an Er 3+ ion using electron spin echo envelope modulation (ESEEM) spectroscopy. ESEEM spectroscopy is a powerful tool because it can determine the distance and coordination number of ligands in a mediumrange structure because very fine interference signals, which are unresolved in conventional continuous wave (CW)-electron paramagnetic resonance (EPR) spectroscopy, are observable by time domain measurements; i.e., it provides information on the medium-range structure around a specific paramagnetic species and quantitative results are obtained by a simulation of the spectrum shape.…”
Section: Mechanism Of Codoping Effectmentioning
confidence: 99%
“…On the other hand, the formation of CeB complex was not observed, and, instead, the segregation of CeO 2 was enhanced. Saitoh et al 75) applied ESEEM spectroscopy and elucidated that a Ce ion was preferentially surrounded by four PO 4 units in the CeP-codoped silica glass while a Ce ion was surrounded by 0.8 BO 3 unit as speculated from the chemical composition of CeB-codoped silica glass. 79) They concluded that the coordination selectivity of the PO 4 unit to Ce is ³10 times larger than that of the SiO 4 unit, whereas the BO 3 unit has no selectivity (³1).…”
Section: Mechanism Of Codoping Effectmentioning
confidence: 99%
“…3)18) Most of RE-Al codoped silica glasses for optical application have been synthesized by vapor phase methods, such as the vapor-phase axial deposition and chemical vapor deposition (CVD), 3),4),12), 16) because these methods are suitable to suppress the incorporation of metallic impurities. However, the vapor pressure of RE compounds is often low, making the direct vapor-phase loading of RE ions into silica glass difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Small changes in composition of crystalline materials can lead to large changes in their electronic properties, such as optical absorption and electrical conductivity (1). Similarly, a small concentration of (co)dopants in amorphous materials can be used to control their optical properties (2,3). Glass properties are typically controlled by varying composition or processing conditions (4).…”
mentioning
confidence: 99%